Identification of a new DMD gene deletion by ectopic transcript analysis. Issue 9 (September 1992) - Rininsland, F; Hahn, A; Niemann-Seyde, S; Slomski, R; Hanefeld, F; Reiss, J
Abstract : The detailed genetic analysis of the Duchenne/Becker muscular dystrophy gene is hindered by the large number of exons involved and their separation by huge introns. These problems can be overcome by the analysis of mRNA rather than genomic DNA and ectopic transcripts derived from peripheral blood lymphocytes provide a convenient source of material. Using reverse transcription and nested PCR, we show here a comprehensive strategy for the rapid and complete analysis of the coding sequences from complex genes and illustrate its potential by the identification of a hitherto undescribed single exon deletion.